The impact of Eco-innovation on corporate carbon performance - Zhang, Meijuan (2022)
According to the International Energy Agency (IEA), the primary element that may possibly result in more than 60% of the desired carbon reductions is projected to be Eco-innovation. This paper examines the effects of Eco-innovation and carbon performance based on the panel data of S&P500 from 2016 to 2020. The results indicate that Eco-innovation is positively associated with carbon performance. The effect holds after addressing the endogeneity problem through the Generalized Method of Moments for Dynamic Systems (GMM) test. The further investigations reveal that gender diversity could strengthen the relationship between Eco-innovation and carbon performance, while the CSR committee and independent board do not.